APPLICATION OF THE JURISPRUDENTIAL LEARNING MODEL TO IMPROVE STUDENT CHARACTER AND LEARNING ACHIEVEMENT (Study on Civics Subjects in Class IX of SMP Negeri 2 Seluma) - Lenda Wati; Bambang Sahono (UNIB Press, 2019)
The purpose of this study is to describe, (1) How the application of Jurisprudential learning models can improve students' character, (2) Jurisprudential learning models can improve student learning achievement, and (3) Effectiveness of the application of Jurisprudential learning models to improve student learning achievement . This study used the classroom action research method followed by quasi-experiments. Data collection is done by observation, and learning achievement tests. Data analysis using descriptive analysis and different test.Classroom action research subjects were students of class IX A, while the experimental class IX B and control class IX C. The results showed that the application of Jurisprudential learning models can improve the character and learning achievement of students, and the application of effective Jurisprudential learning models can improve learning achievement PPKn at Seluma 2 Public Middle School